The Benefits of Walking Your Talk: Aggregate Effects of Behavioral Integrity on Guest Satisfaction, Turnover, and Hotel Profitability. (August 2018) - Simons, Tony; McLean Parks, Judi; Tomlinson, Edward C.
Extending theory on behavioral integrity to department and business unit levels of analysis, we examined a chain of relationships culminating in operational and financial performance measures. Specifically, we analyzed survey data from 6, 800 workers from 76 same-branded US hotels and integrated it with operational and financial data. Latent variables structural equation modeling and path analyses showed strong associations between manager behavioral integrity and worker turnover, customer satisfaction, and hotel profitability. In fact, behavioral integrity accounted for 13% of the variance in profitability across hotels. This relationship was partially mediated by trust in managers, affective commitment, and discretionary service behavior.